2005
DOI: 10.1063/1.2120913
|View full text |Cite
|
Sign up to set email alerts
|

High-performance GaN-based light-emitting diode using high-transparency Ni∕Au∕Al-doped ZnO composite contacts

Abstract: We report on a high-transparency low-resistance composite contact structure on p-GaN for light-emitting diode applications. The structure consists of a thin Ni ͑5 nm͒ /Au ͑5 nm͒ layer overcoated with a sputtered Al-doped ZnO ͑170 nm͒ layer. Enhancement in light emission intensity as high as 74% at 40 mA and forward operating voltages in the range of 3.36-3.48 V at 20 mA are obtained for these devices using a two-step thermal annealing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Photon recycling is an effect describing a re-capture of the photons propagating outside an escape cone and re-emission of photons from the active layer into the escape cone, enhancing the extraction efficiency in LEDs 17 . Photon recycling effect is usually unapparent in the quantum-well (QW) based LEDs because of low optical absorption in the thin QW layer 18 . This effect could be enhanced through an interaction between a high-absorption material and an evanescent field from optical cavity modes.…”
Section: Introductionmentioning
confidence: 99%
“…Photon recycling is an effect describing a re-capture of the photons propagating outside an escape cone and re-emission of photons from the active layer into the escape cone, enhancing the extraction efficiency in LEDs 17 . Photon recycling effect is usually unapparent in the quantum-well (QW) based LEDs because of low optical absorption in the thin QW layer 18 . This effect could be enhanced through an interaction between a high-absorption material and an evanescent field from optical cavity modes.…”
Section: Introductionmentioning
confidence: 99%
“…Before fabrication, a circular transmission line method (CTLM) was used to evaluate the as deposited AZO/p-GaN and AZO/(oxidized Ni/Au) contacts. It is found that AZO/p-GaN and AZO/(oxidized Ni/Au) are Schottky and ohmic contacts, respectively [9][10]. Figure 1 illustrates the key fabrication processes of the SR-LEDs.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Thus the intrinsic polarization states are altered, and in turn electroluminescence (EL) characteristics, and irradiative recombination efficiency are affected [5][6][7]. In this work, we managed to alleviate this situation by inserting a sputter-deposited aluminum-doped zinc-oxide (AZO) layer between p-side ohmic contacts (oxidized Ni/Au) and the underlying metal layers for its less mismatching CTE and good as-deposited optical properties [8][9][10]. In addition, the oxidized Ni/Au was patterned to expose p-GaN to form a Schottky blocking region with the AZO layer under the n-electrode area [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Ni/AZO and NiO/AZO as current spreading layers (CSLs) of LEDs were employed for low-resistance ohmic contacts due to their high work function and the formation of Ga vacancies near the surface of p-GaN. [17][18][19][20] Additionally, a facile growth of ZnO nanorods may be more compatible with the AZO films.…”
Section: Introductionmentioning
confidence: 99%